Desulfovibrio feeding Methanobacterium with electrons in conductive methanogenic aggregates from coastal zones. (1st September 2021) - Zheng, Shiling; Li, Meng; Liu, Yang; Liu, Fanghua
Highlights: Desulfovibrio and Methanobacterium species were the most abundant in aggregates. Desulfovibrio species highly expressed genes for cytochromes, pili and flagella. Desulfovibrio strain JY contributed to aggregate conductivity. Methanobacterium might directly accept electrons from Desulfovibrio . Abstract: Geobacter, as a typical electroactive microorganism, is the "engine" of interspecies electron transfer (IET) between microorganisms. However, it does not have a dominant position in all natural environments. It is not known what performs a similar function as Geobacter in coastal zones. Metagenomic and metatranscriptomic analysis revealed that Desulfovibrio and Methanobacterium species were the most abundant in electrochemically active aggregates. Metatranscriptomic analysis showed that Desulfovibrio species highly expressed genes for ethanol metabolism and extracellular electron transfer involving cytochromes, pili and flagella. Methanobacterium species in the aggregates also expressed genes for enzymes involved in reducing carbon dioxide to methane. Pure cultures demonstrated that the isolated Desulfovibrio sp. strain JY contributed to aggregate conductivity and directly transferred electrons to Methanothrix harundinacea, which is unable to use H2 or formate. Most importantly, further coculture studies indicated that Methanobacterium strain YSL might directly accept electrons from the Desulfovibrio strain JY for the reduction of carbon dioxide to methane in the aggregate. This finding suggested that the possibility of DIET by Desulfovibrio similar to Geobacter species in conductive methanogenic aggregates can not be excluded. Graphical abstract: Image, graphical abstract